Polish Women in Exile to Siberia in the 19th Century – Autobiographical Reflection in Women’s Narratives - Michalska-Bracha, Lidia (Respectus Philologicus, 2018)
[full article and abstract in English] The paper discusses the issues related to the biographical research perspective and the role of ego-documents in modern humanities. These considerations focus on autobiographical narratives of women exiled to Siberia in the 19th century, both those who were sentenced or went there voluntarily. Different forms of women’s narratives were analysed, namely a memoir of Helena Skirmuntowa (1827–1874), written in the years 1863–1867, and a diary of Maria Obuchowska-Morzycka (1841–1911?), who wrote it 40 years after her life in exile. The autobiographical research model adopted in the paper focuses not only on the questions regarding the autobiographical context of ego-documents but also on biographical and autobiographical identity of the authors, connected with the description of their life, experiences, emotions as well as their attitude to the outside world and relations with other people.